CONTROL OF THE ROTOR SYSTEM - Imanbayeva, Akmaral Karimovna (Recent Contributions to Physics, 2008)
In the present, work the mathematical model of the rotor system with the automatic balancing devices taking into account of the engine characteristics is offered. The basic purpose is construction of a control law, allowing realization of unbalanced rotor acceleration under restrictions on a drive rotating moment. The various criteria having substantial physical meaning are discussed, such as minimization of time for achievement of the set angular velocity, spent in process of energy acceleration, average value of the resonance amplitudes, maximization of angular velocity after acceleration finishing, and also maximization of the rotating moment value in acceleration process.